2016
DOI: 10.1007/s11930-016-0076-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-offending Pedophiles

Abstract: Non-offending pedophiles are a unique population of individuals who experience sexual interest in children, but despite common misperceptions, have neither had sexual contact with a child nor have accessed illegal child sexual exploitation material. An emerging body of research has examined the prevalence of pedophilic interests, characteristics of nonoffending pedophiles, correlates of pedophilic interests, and stigma associated with pedophilia. Treatment programs are beginning to produce findings regarding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
104
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(119 citation statements)
references
References 50 publications
(66 reference statements)
3
104
0
5
Order By: Relevance
“…Participant 4Whilst private therapy is an option for some, for other individuals within the target group it is not financially viable, and with UK prevention in its 'embryonic stages' (Participant 4) there is an apparent lack of opportunities for help. This is recognised within the literature; compared to treatment of paedophiles involved in the CJS, treatment with non-offending individuals is considered underdeveloped (Cantor & McPhail, 2016). In times of little available funding it may be that there are few current options for non-offending paedophiles because primary and secondary prevention interventions are difficult to evidence (Brown & Saied-Tessier 2015) and…”
Section: Subordinate Theme 32: Lack Of Adequate Servicesmentioning
confidence: 99%
“…Participant 4Whilst private therapy is an option for some, for other individuals within the target group it is not financially viable, and with UK prevention in its 'embryonic stages' (Participant 4) there is an apparent lack of opportunities for help. This is recognised within the literature; compared to treatment of paedophiles involved in the CJS, treatment with non-offending individuals is considered underdeveloped (Cantor & McPhail, 2016). In times of little available funding it may be that there are few current options for non-offending paedophiles because primary and secondary prevention interventions are difficult to evidence (Brown & Saied-Tessier 2015) and…”
Section: Subordinate Theme 32: Lack Of Adequate Servicesmentioning
confidence: 99%
“…That is, we used the tendency to suppress unwanted thoughts and an index of psychological wellbeing as indirect proxies of internalized stigma among MAPs, while selfreported frequency of actively avoiding children was used at the outset of the project as an indication of self-perceived risk of committing acts of sexual abuse (though see above for an alternative interpretation of this construct that still reflects the internalization of stigma). This strategy was used such as to not prime themes related to stigmatization, and to not implicitly assume this population were at an enhanced risk of sexually offending against children (Cantor & McPhail, 2016). In addition, our question about help-seeking behaviors was nonspecific, and so responses could include a combination of participants accessing professionally delivered schemes and more informal social supports.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…While sexual interests towards minors and other paraphilias have been identified as key risk factors for sexual (re-)offending (Hanson & Morton-Bourgon, 2005;Helmus, Ó Ciardha, & Seto, 2015), contemporary research in Germany has reported that fewer than half of all individuals convicted of child abuse offenses actually have a pedophilic sexual preference (Schmidt, Mokros, & Banse, 2013). Further, there is an unknown number of individuals with pedophilia as their predominant sexual arousal pattern (as well as MAPs with other ages of attraction) in the community, who never commit any offenses at all (Cantor & McPhail, 2016). Some estimates place the specific prevalence of pedophilia within the general (male) population at between <.1-5% (Dombert et al, 2016;Seto, 2008).…”
mentioning
confidence: 99%
“…For instance, perceived stigmatization was associated with increased levels of fear related to being 'discovered' or 'outed' as a pedophile, as well as being predictive of social isolation, perceived social distance from what they may perceive as being the 'normal' population, and decreased self-esteem. Observing these relationships is important as they have significant implications for public health from both a mental wellbeing and child abuse prevention perspective (Cantor, 2014;Cantor & McPhail, 2016). From a wellbeing perspective, people with sexual interests in children have reported that professionals working with them appear to focus more on risk reduction (e.g., controlling sexual urges), despite them preferring to be supported in relation to the more general psychological wellbeing issues mentioned above (B4U-ACT, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Instead, these individuals seek out a range of online fora (e.g., Virtuous Pedophiles and B4U-ACT) wherein they can communicate with and be supported by other non-offending people with pedophilic interests in a safe environment. The scale of the use of these fora suggests that the level of supply of services to support this group is far lower than the demand for them (B4U-ACT, 2011; Cantor & McPhail, 2016), in spite of professional and mental health services that target this population being shown to both increase mental wellbeing and reduce dynamic risk factors associated with sexual offending (Beier et al, 2015; for a broader discussion of these risk factors, see Gillespie, Mitchell, Fisher, & Beech, 2012).…”
Section: Introductionmentioning
confidence: 99%